Analisis Yuridis Ketentuan Pasal 152 Ayat (3) Undang-Undang Republik Indonesia Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah Mengenai Kewenangan Pembatalan Peraturan Daerah Kabupaten/Kota oleh Menteri Dalam Negeri - Anggalana ANGGALANA (Universitas Bandar Lampung (UBL), 2017)
Regional autonomy is the transfer of authority from the central government to local governments in the context of the implementation of government affairs in the region. This also applies to the delegation of authority from the central government to regional governments to administer government affairs in their autonomous regions based on the principle of decentralization and co-administration, as well as the authority in the formulation of regional regulations by the regional government together with the Regional People's Legislative Assembly Regional. Starting from the planning stage, the discussion until validation and enactment must be based on applicable laws and regulations. In addition, the regional regulations should also be coordinated by the regional government to the central government, either the Provincial Government as a representative of the central government in the region or with the central government in this case the Ministry of Home Affairs in order to harmonize with higher laws and regulations equivalent to goals and able to support each other. If in the coordination related to the establishment of the regional regulation is contrary to the principle of legislative formation, the central government has the authority to cancel the regional regulations in accordance with the prevailing laws and regulations.